齿形链传动在汽车变速箱及分动箱中的应用 - 叶斌; 王洪军; 王丹 (Jixie chuandong)
New silent chains with diverse structures and diverse meshing mechanisms are used in gearbox and transfer case for automobile gradually.On the basis of discussing the important technical characteristics of silent chain,the application advantages of silent chain drive in automotive gearbox and transfer case are emphatically introduced and the development status of the hybrid car and good market prospect of four-wheel drive automobile are analyzed.It has an important reference value for the chain industrial restructuring.